2000
DOI: 10.4049/jimmunol.165.5.2588
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Novel CXC Chemokine Macrophage Inflammatory Protein-2γ Chemoattractant for Human Neutrophils and Dendritic Cells

Abstract: Chemokines play important roles in leukocyte trafficking as well as function regulation. In this study, we described the identification and characterization of a novel CXC chemokine from a human dendritic cell (DC) cDNA library, the full-length cDNA of which contains an open reading frame encoding 111 aa with a putative signal peptide of 34 aa. This CXC chemokine shares greatest homology with macrophage inflammatory protein (MIP)-2αβ, hence is designated as MIP-2γ. Mouse MIP-2γ was identified by electrocloning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 35 publications
3
97
0
1
Order By: Relevance
“…Using gene arrays, we compared the expression of chemokines by resting vs TLR2-activated odontoblasts. We observed the expression by resting odontoblasts of CCL2, CXCL12, and CXCL14, three chemokines known to drive iDCs recruitment in vitro (11,31,32,33). However, the chemokine the most strongly expressed by resting odontoblasts was CCL26, a natural antagonist for CCR1, CCR2, and CCR5 (34).…”
Section: Figurementioning
confidence: 83%
“…Using gene arrays, we compared the expression of chemokines by resting vs TLR2-activated odontoblasts. We observed the expression by resting odontoblasts of CCL2, CXCL12, and CXCL14, three chemokines known to drive iDCs recruitment in vitro (11,31,32,33). However, the chemokine the most strongly expressed by resting odontoblasts was CCL26, a natural antagonist for CCR1, CCR2, and CCR5 (34).…”
Section: Figurementioning
confidence: 83%
“…Human CXCL14, alternatively called BRAK and MIP-2␥, is constitutively produced in healthy epithelial tissues such as skin and gut. CXCL14 is also present in various tumors of epithelial origin, but the level of expression is heterogeneous, with the majority showing a downregulation with respect to healthy tissue (4,9,15,19,43,44,46). Recently, we have shown that human CXCL14 is selective for blood monocytes and CD14 ϩ DC precursors, either derived from CD34 ϩ hematopoietic progenitor cells or isolated from blood (19,42).…”
mentioning
confidence: 99%
“…CXCL14 is a chemokine with unknown function and receptor selectivity (4,9,15). Human CXCL14, alternatively called BRAK and MIP-2␥, is constitutively produced in healthy epithelial tissues such as skin and gut.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that mouse Tim-3 is involved in the interactions between Th1 cells and macrophages, which results in the expansion and activation of macrophages. As a homologue of mouse Tim-3, (14)(15)(16). One of the full-length cDNAs encodes a 301-residue type I integral membrane glycoprotein.…”
Section: Introductionmentioning
confidence: 99%